ANTIBIOTIC SUSCEPTIBILITY PROFILE OF GERMS RESPONSIBLE FOR NOSOCOMIAL INFECTIONS IN THE SURGICAL AND INTENSIVE CARE UNITS OF THE MILITARY HOSPITAL REGION N° 1, CAMEROON - Ayangma, Celestin Roger; Voundi, Esther; Mandah, Darrelle Meli; Kabir, Haamit Abba; Kona, Stephane Francois; Djoubairou, Ben Ousmanou; Medi, Christiane Sike; Kemajou, Bianca; Hamadou; Ngaba, Guy (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Antimicrobial resistance is a real public health threat. The general objective of our study was to identify the germs associated with nosocomial infections and to study the antimicrobial susceptibility profile. Methodology: We conducted a cross-sectional analytical study in the surgical and intensive care units of the Number 1 Military Regional Hospital. The susceptibility study was done according to the CA-SFM guidelines. To determine the factors associated with nosocomial infection, a multivariate analysis was performed by logistic regression. The strength of the association was measured using the Odd Ratio (OR) and its 95% confidence interval (95% CI). Results: A total of 15 of 83 patients had a nosocomial infection (18.1%). ASA 3 (OR [95% CI]=15.65 [2.53-138.80]), ASA 1 (OR [95% CI]=0.11 [0.02-0.46]), dirty surgery (OR [95% CI]=2.88 [0.31-22.20]), absence of comorbidities (OR [95% CI]=0.23 [0.07-0.72]) and diabetes (OR [95% CI]=31.16 [3.87-805.55]) were associated with nosocomial infection (p<0.05). Escherichia coli (4; 23.5%) and Pseudomonas aeruginosa (3; 17.6%) were the most isolated. Strains showed better sensitivity to fosfomycin, chloramphenicol and levofloxacin. Candida sp strains were sensitive to the antifungal agents tested. Conclusion: A low rate of sensitivity to the tested antibiotics was observed. Regular monitoring of the sensitivity profile of germs responsible for nosocomial infections seems to be imperative in the fight against AMR.